PERSPEKTIF PENGAJARAN SASTRA STRATTA ABAD 21 - Armet, Armet -; Mana, Lira Hayu Afdetis (Penerbit Widina, Widina Media Utama, 2023)
In the development of the 21st century world, schools are required to be able to keep up with their students in the era of progress, due to the rapid development of information and communication technology in all aspects of life, including in terms of learning in schools. The teaching of literature has recently been hampered a bit so that it does not get maximum results. This study examines the perspective of teaching literature in Stratta abab 21. The aim of this research is to see the relationship of teaching literature in class XI textbooks of the 2013 curriculum towards the 21st century: the perspective of teaching literature in Stratta. This research is a qualitative research. The method in this research is descriptive. Based on the results of the study, the use of the Stratta model in the 2013 curriculum textbooks for class XI was not fully effective in teaching literature due to the lack of variations in the learning model used by the teacher. The concept of teaching literature in the 2013 curriculum textbook for class XI is apperception, performance and formative tests. While the teaching concept of Stratta is exploration, interpretation and recreation (deepening).ABSTRAKPerkembangan dunia abad ke-21 ini sekolah dituntut untuk bisa mengimbangi siswanya pada era kemajuan, karena dengan berkembang pesatnya teknologi informasi dan komunikasi dalam segala aspek kehidupan, termasuk dari segi pembelajaran di sekolah. Pengajaran sastra belakangan ini sedikit mendapat hambatan sehingga tidak mendapatkan hasil yang maksimal. Penelitian ini mengkaji tentang bagaimana perspekstif pengajaran sastra Stratta abab 21.Tujuan penelitian ini untuk melihat hubungan pengajaran sastra dalam buku teks kelas XI kurikulum 2013 menuju abad 21: perspektif pengajaran sastra Stratta. Penelitian ini merupakan penelitian kualitatif. Metode dalam penelitian ini adalah deskriptif. Berdasarkan hasil penelitian bahwa penggunaan model Stratta dalam buku teks kurikulum 2013 kelas XI belum sepenuhnya efektif dalam pengajaran sastra dikarenakan kurangnya variasi model pembelajaran yang digunakan guru. Adapun konsep pengajaran sastra dalam buku teks kurikulum 2013 kelas XI adalah apersepsi, unjuk kegiatan dan tes formatif. Sedangkan konsep pengajaran Stratta yaitu penjelajahan, interpretasi dan rekreasi (pendalaman).